The Legal Dilemma of the 19% Reciprocal Tariff between the Republic of Indonesia (RI) and the United States (US): A Critical Review and Bilateral Policy Implications - Laurenzia Luna; Aurrelia Yulia Shanra; Riviona Dani; Michelin Fanesia Ekadi (IHSA Institute, 2025)
Trade between Indonesia and the United States plays a strategic role in maintaining economic stability in the Indo-Pacific region. The change in the joint tariff policy, especially when the US tariff is set at 32% and then lowered to 19%, reflects the complex dynamics between national economic interests and obligations of International Law (IL). This paper is a law that the Indonesian government can use to respond to United States (US) retaliatory tariffs and also review its compliance with international trade principles, such as Most Favored Nation (MFN), National Treatment (NT), It was a negotiation of goodwill within the framework of the World Trade Organization (WTO), General Agreement on Tariffs and Trade (GATT) 1994. This study was normative by a conceptual and comparative approach to International Law (IL). The data was obtained through a literature study of legislation rules, scientific journals, and official statements of the public. Research results show that the application of reciprocal tariffs in the United States (US) has the potential to violate the principle of non-discrimination and development in bilateral trade. The bilateral settlement through diplomacy is considered the most effective step in maintaining trade stability while protecting the legitimacy of Indonesian law at the international level, emphasizing the importance of a balance between personal protection and compliance with international law in trade formulation. The improvement of law-based economic diplomacy and institutional coordination is key to ensuring that Indonesia's tariff policy remains balanced, credible, and sustainable